2012
DOI: 10.1177/1059840512471397
|View full text |Cite
|
Sign up to set email alerts
|

Child-to-Child Training for Prevention of School Injuries in Odemis, Turkey

Abstract: Students encounter many risks for injury, which can impact their health and educational success; prevention of these injuries are paramount for school nurses. These article report results of a study conducted to determine the efficacy of training given to children regarding prevention of school injuries and to compare the effectiveness of instructor-to-child training to that of the child-to-child training method in affecting student attitudes toward the prevention of school injuries. An interventional teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Thus, it was concluded that peer-led dietary education could be used as an alternative approach in future school-based health education interventions, even though it did not lead to any changes in the children's diet self-efficacy and behaviors in this study. This result supported the findings of other studies in which peer-led education was implemented to prevent school injuries and to improve students' oral health behaviors (19,30).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, it was concluded that peer-led dietary education could be used as an alternative approach in future school-based health education interventions, even though it did not lead to any changes in the children's diet self-efficacy and behaviors in this study. This result supported the findings of other studies in which peer-led education was implemented to prevent school injuries and to improve students' oral health behaviors (19,30).…”
Section: Discussionsupporting
confidence: 88%
“…Peer-led training has been found to increase knowledge, attitudes, and beliefs, and to promote health behaviors more than adult-led training (13,14). Peer-led training has been used in the school environment for the following purposes: prevention of obesity (15), prevention of substance abuse (16), prevention of smoking (17), nutrition promotion (14,18), and prevention of injuries (19). In schools lacking nurses, promoting students' healthy dietary habits through peer-led training should be considered as a method that will contribute to the promotion of public health.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher considers that child-to-child education is suitable for providing health education. There are different studies showing that child-to-child education is effective in the literature 5,11,12,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The scale can be applied to all students of primary school age, except for the first-year students. Items 2,3,4,5,7,10,12,20,21,22,26,32,34,36,37,38, and 39 are reverse scored. As a result, each student is able to obtain a minimum of 40 and a maximum of 200 points.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation